2006
DOI: 10.1186/1471-2164-7-325
|View full text |Cite
|
Sign up to set email alerts
|

Alternative splicing and differential gene expression in colon cancer detected by a whole genome exon array

Abstract: Background: Alternative splicing is a mechanism for increasing protein diversity by excluding or including exons during post-transcriptional processing. Alternatively spliced proteins are particularly relevant in oncology since they may contribute to the etiology of cancer, provide selective drug targets, or serve as a marker set for cancer diagnosis. While conventional identification of splice variants generally targets individual genes, we present here a new exon-centric array (GeneChip Human Exon 1.0 ST) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
322
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 315 publications
(338 citation statements)
references
References 56 publications
16
322
0
Order By: Relevance
“…The exon array assesses the abundance of all exons from both empirically curated mRNA sequences and computationally predicted transcripts. In addition to gene level changes, the exon array can also reveal variations in individual exons that may result from alternative splicing, promoter utilization, termination, and polyadenylation (27)(28)(29). Principle component analysis indicates that the data points for NELF-A, -C, and -E knockdown cells were all clustered with each other and well separated from those of the control knockdown cells (supplemental Fig.…”
Section: Nelf-a -C and -E Knockdown Results In Reduced Expression Omentioning
confidence: 99%
“…The exon array assesses the abundance of all exons from both empirically curated mRNA sequences and computationally predicted transcripts. In addition to gene level changes, the exon array can also reveal variations in individual exons that may result from alternative splicing, promoter utilization, termination, and polyadenylation (27)(28)(29). Principle component analysis indicates that the data points for NELF-A, -C, and -E knockdown cells were all clustered with each other and well separated from those of the control knockdown cells (supplemental Fig.…”
Section: Nelf-a -C and -E Knockdown Results In Reduced Expression Omentioning
confidence: 99%
“…Recently, studies have suggested that lncRNA expression profiling may be achieved by mining existing microarray data because some probes uniquely mapping to lncRNAs are fortuitously represented on these arrays [33,34] . The Affymetrix Human Exon 1.0 ST array consists of over 6.5 million individual probes designed along the entire length of the gene as opposed to just the 3' end, providing a unique platform for mining lncRNA profiles [35,36] . The lncRNA list used in this study was retrieved from Ensembl and is equivalent to the GENCODE lncRNA data set.…”
Section: Discussionmentioning
confidence: 99%
“…These designs have facilitated analyses of genome-wide alternative splicing in human, mouse, and chimp (Srinivasan et al 2005;Boutz et al 2007;Calarco et al 2007;Ip et al 2007;Ni et al 2007), as well as detection of the global impact of specific splicing factors or environmental stimuli on splicing regulation (Park et al 2004;Hung et al 2007;Makeyev et al 2007;Pleiss et al 2007a,b). A very high-density ''exon array'' containing probes in essentially all known and predicted human exons was recently developed by Affymetrix (Gardina et al 2006). Generally speaking, these array platforms appear able to identify a subset of AS events with high confidence, but have an unknown and probably substantial rate of false negatives.…”
Section: Global Analyses Of Splicing Regulationmentioning
confidence: 99%